7 Is the New 8: Improving Adherence to Restrictive PRBC Transfusions in the Pediatric ICU. Issue 1 (January 2020) - Badke, Colleen M.; Borrowman, Julie A.; Haymond, Shannon; Rychlik, Karen; Malakooti, Marcelo R.
Abstract : ABSTRACT: Up to 30%–40% of children admitted to the pediatric intensive care unit (PICU) have anemia, and approximately 15% receive packed red blood cell (pRBC) transfusions. Current literature supports a pRBC transfusion threshold of hemoglobin less than or equal to seven for most PICU patients. Our objective was to determine pRBC transfusion rates, assess compliance with transfusion guidelines, understand patient-level variables that affect transfusion practices, and use cross-industry innovation to implement a practice strategy. This was a pre–post study of pediatric patients admitted to our PICU. We collected baseline data on pRBC transfusion practices. Next, we organized an innovation platform, which generated multi-industry ideas and produced an awareness campaign to effect pRBC ordering behavior. Innovative educational interventions were implemented, and postintervention transfusion practices were monitored. Statistical analysis was performed using linear mixed models. A p value < .05 was considered statistically significant. At baseline, 41% of pRBC transfusions met restrictive transfusion guidelines with a pretransfusion hemoglobin less than or equal to 7 g/dl. In the postintervention period, 53% of transfusions met restrictive transfusion guidelines (odds ratio 1.66, 95% confidence interval 1.21–2.28). Implementation of a behavioral campaign using multi-industry innovation led to improved adherence to pRBC transfusion guidelines in a tertiary care PICU.